International Spillovers of Output Growth and Output Growth Volatility: Evidence from the G7 - Nikolaos Antonakakis; Harald Badinger (FIW - Research Centre International Economics, 2010)
This paper examines the transmission of GDP growth and GDP growth volatility among the G7 countries over the period 1960 q1 - 2009 q3, using a multivariate generalized autoregressive conditional heteroskedasticity (MGARCH) model to identify the source and magnitude of spillovers. Results indicate the presence of positive own-country GDP growth spillovers in each country and of cross-country GDP growth spillovers among most of the G7 countries. In addition, the large number of significant own-country output growth volatility and cross-country output growth volatility spillovers indicates that output growth shocks in most of the G7 countries affect output growth volatility in the remaining others. An additional finding is that U.S. is the dominant source of GDP growth volatility transmission, as its volatility exerts a significant unidirectional spillover to all remaining G7 countries.
Keywords: E32; F41; F44; 330; Business cycle transmission; Spillovers; Recession